2021
DOI: 10.18041/1900-3803/entramado.1.6538
|View full text |Cite
|
Sign up to set email alerts
|

Mus musculus: biomodelo de expresión de Desyodinasa (DIO3) y Transtiretina (TTR) en el desarrollo placentario

Abstract: Introducción: El correcto funcionamiento del eje hipotálamo-hipófisis-tiroides es indispensable para el crecimiento y desarrollo embrionario-fetal, al intervenir en la diferenciación de los tejidos, el desarrollo cerebral y somático, la maduración ósea y la regulación del metabolismo. El paso de las hormonas tiroideas maternas al feto a través de la placenta depende de transportadores transmembrana, enzimas desyodinasas (DIO2 y DIO3) y proteínas transportadoras (TTR). Objetivo: Identificar las zonas de expresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Also,Landers et al (2018) found that human derived trophoblast cells can take up TTR and the TTR-T4 complex through cell surface receptor SR-B1. This is supported by data showing that SR-B1-ko cells had a significantly reduced uptake of TTR.Not surprisingly, TTR has a robust expression on the maternal side of the placenta and is also present in fetal placenta (mouse labyrinth zone)(Falla-Zuñiga et al, 2021;Landers et al, 2018;Peng et al, 2020). TTR's presence in the trophoblast has been reported in humans starting the sixth week of gestation and reaches a plateau around 13 weeks, remaining elevated by term(Patel et al, 2011a(Patel et al, , 2011b.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…Also,Landers et al (2018) found that human derived trophoblast cells can take up TTR and the TTR-T4 complex through cell surface receptor SR-B1. This is supported by data showing that SR-B1-ko cells had a significantly reduced uptake of TTR.Not surprisingly, TTR has a robust expression on the maternal side of the placenta and is also present in fetal placenta (mouse labyrinth zone)(Falla-Zuñiga et al, 2021;Landers et al, 2018;Peng et al, 2020). TTR's presence in the trophoblast has been reported in humans starting the sixth week of gestation and reaches a plateau around 13 weeks, remaining elevated by term(Patel et al, 2011a(Patel et al, , 2011b.…”
mentioning
confidence: 57%
“…During this period, DIO2 increases the availability of local T3 for the development and differentiation of placental tissues, as well as contributing to the bioavailability of T3 in the development of fetal organs. DIO3 expression has also been seen in the cytoplasm and plasma membranes of syncytium and cytotrophoblast from the mouse labyrinth zone during mid‐pregnancy (Falla‐Zuñiga et al, 2021; Galton et al, 1999; Huang et al, 2003). In the third trimester, it is DIO3 that is mainly expressed.…”
Section: Th Metabolism In the Placentamentioning
confidence: 99%
See 1 more Smart Citation